Social pedagogy: historical traditions and transnational connections - Schugurensky, Daniel; Silver, Michael (Education Policy Analysis Archives, 2013)
With over 150 years of history, social pedagogy is both an interdisciplinary scholarly field of inquiry and a field of practice that is situated in the intersection of three areas of human activity: education, social work and community development. Although social pedagogy has different emphases and approaches depending on particular historical and geographical contexts, a common theme is that it deals with the connections between educational and social dynamics, or put in a different way, it is concerned with the educational dimension of social issues and the social dimensions of educational issues. The first part of this paper analyzes the history of the field of social pedagogy since its origins until today, with a focus on transnational flows between Europe and the Americas. The second part of the paper discusses the main issues raised in this special issue of EPAA, and extracts the main threads and connections among the different papers included in the volume.